Kajian Literatur Pemanfaatan Sistem Informasi Geografis Untuk Pariwisata Indonesia - Aji, Ridho Catur Novi; Sukmasetya, Pristi (Jurnal Ilmiah Sistem Informasi (JISI), 2022)
The tourism sector as an economic activity has become a potential mainstay and development priority for a number of countries. Especially for developing countries such as Indonesia which has a large area potential with a large enough tourist attraction. The potential of tourism in Indonesia stretches widely from the Province of Nangroe Aceh Darussalam to the Province of Papua with all the diversity of tourism objects, arts and culture and the availability of tourism supporting facilities and infrastructure that are capable of driving the people's economy. So that the number of tourists continues to increase and does not experience saturation of tourist objects, there needs to be development in the tourism sector. The purpose of this study was to determine the distribution of natural and cultural tourism in Indonesia. To achieve this goal, research methods are used by mapping the distribution of natural and cultural tourism in Indonesia, by plotting the tourist sites. In order to determine the distribution of natural and cultural tourism in Indonesia, descriptive research methods are used by describing maps. From this description, it is necessary to have an information system that provides information about tourist sites in Indonesia. One of the presentations of this tourism information is through displaying in the form of data or information related to geographical conditions in the territory of Indonesia, this system is often known as the Geographic Information System (GIS). The existence of a geographic information system will provide an alternative convenience for the public to find information about tourist locations and information in Indonesia and provide convenience to the Department of Culture and Tourism in Indonesia in processing data on information on tourist locations in Indonesia.